2014
DOI: 10.1186/s40510-014-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

A 15-month evaluation of bond failures of orthodontic brackets bonded with direct versus indirect bonding technique: a clinical trial

Abstract: BackgroundThe purpose of this clinical longitudinal study was to investigate the effectiveness of indirect bonding technique evaluating the number of bond failures which occurred during treatment.MethodsFifty-two patients were selected and divided into two groups: group A (33 patients) bonded with the direct technique and group B (19 patients) bonded with the indirect technique. The number and date of bracket failure were recorded for over 15 months. Moreover, also the effect of crowding level on bracket failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 25 publications
5
43
0
6
Order By: Relevance
“…2,12 The higher bond failure rate for first and second molar tubes can be related to the difficulty of avoiding contamination, manipulation of the tube during bonding, and higher forces of mastication in the molar region. 13 In an investigation using a sample size of 128 patients, no significant difference between bracket failure rates of incisors vs premolars was found. 8 In our study, we found a significantly higher failure rate for orthodontic appliances in the mandible compared with the maxilla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,12 The higher bond failure rate for first and second molar tubes can be related to the difficulty of avoiding contamination, manipulation of the tube during bonding, and higher forces of mastication in the molar region. 13 In an investigation using a sample size of 128 patients, no significant difference between bracket failure rates of incisors vs premolars was found. 8 In our study, we found a significantly higher failure rate for orthodontic appliances in the mandible compared with the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…The failure rate for indirect bonding of brackets and tubes has been found to be the same as or somewhat higher than that of direct bonding. 13 Even if the direct method should result in fewer failures, indirect bonding has several advantages: more accurate bracket placement, dental assistants can position the indirect bonding trays, a significant reduction of chair time, reduced need for rebonding of brackets during treatment, because of the above, total treatment time can be shorter.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented experiment, the Transbond XT was used in both test groups. It has been used in many studies, [18][19][20][21] so the results can be comparable. The bonding material Transbond SEP Plus has also been proven to be one of the best bonds used in orthodontics.…”
Section: Discussionmentioning
confidence: 99%
“…Transbond XT was developed for orthodontic use. Is one of the most widely used composite resins for bonding of orthodontic appliances [31,32]. Can be regarded as one of standard adhesive systems in orthodontics.…”
Section: Discussionmentioning
confidence: 99%